Influence of Anogeissusleiocarpus Stem Bark Extract on the Fatty Acid Composition in Meat of Broiler Chickens - J. O., Alagbe; M.D, Shittu; Babatunde, Tanimomo, Kayode (European Journal of Life Safety and Stability (2660-9630), 2022)
There is a global increasing awareness on the use of medicinal plants as organic alternatives to antibiotics due to the presence of phytochemicals in them to curb the dangers of antimicrobial resistance, environmental pollution and presence of toxic residues in animal products.This experiment was conducted to evaluate the influence of Anogeissusleiocarpus stem bark extract (ALSB) on the fatty acid composition in meat of broiler chickens. 600 1-day-old broiler chicks (Cobb 500) of mixed sex were randomly assigned to 6 dietary treatments (T1, T2, T3, T4, T5 and T6) of 5 replicates consisting of 20 birds each in a completely randomized design (CRD), The experiment lasted for 56 days, feed and water was fed ad libitum and other management practices were carried out throughout the period of the experiment. Birds in T1 and T2 were fed basal diet with 1.25 g and 1.50 g Oxytetracycline/liter of water while T3, T4, T5 and T6 were fed basal diet with 20, 40, 60 and 80 ml/liter Anogeissusleiocarpus stem bark extract (ALSB) respectively.The results showed that significant (P<0.05) differences were observed in saturated fatty acid (SFA), polyunsaturated fatty acid (PUFA) and omega-6/omega -3 ratio (n-6: n-3) values obtained in the breast and meat composition. Saturated fatty acid (SFA) in breast meat was highest in T1 and T2 (53.10 % and 49.90 %), intermediate in T3 and T4 (40.90 % and 40.02 %) and lowest in T5, T6 (35.92 % and 35.90 %) (P < 0.05). Similarly SFA in thigh meat was maximum at T1 and T2 (50.80 %, 50.60 %), midway T3, T4 (42.11, 41.00 %) and minimum T5, T6 (32.08, 32.00 %) (P < 0.05).PUFA was highest among birds fed (ALSB). It can be concluded that feeding broilers up to 400 mg/kg highly influenced the composition of fatty acid in broiler meat.